Spanish doc to heal her - Baine, Karin (Harlequin medical romance, 2025)
It's often said that home is where the heart is. But Dr. Inés had zero intention of returning to Spain and her controlling family... Until her ex-boyfriend left her with no choice but to work at her father's medical practice. The only ray of hope? Inés's new coworker, Dr. Ángelo, who is as infuriating as he is irresistible. Yet while their attraction burns hotter than the Mediterranean sun, is Inés ready to bring down her barriers and let Ángelo in?